Caracterização de blocos estruturais de concreto com agregados reciclados - Taube, Alexandre dos Santos (2019)
The construction sector is one of the biggest contributors to the waste generated by society. The correct disposal and management of construction waste is becoming an increasingly arduous task. In the same way, adequate raw material for concrete production is scarcer each day. Both recycling and reuse of construction and demolition wastes as well as the use of recycled aggregates are becoming more and more common practices. Several researches have been emerging recently raiming to open new markets for these recycled materials. In this context, the present study analyzed class A structural concrete blocks produced with aggregates from recycled construction waste. The aggregates derived from concrete waste were characterized and differed from the natural aggregates in their finer grain size, higher water absorption, lower specific mass and lower unit mass. Five mix ratios with different replacement ratios of conventional aggregates were tested: 20%, 40%, 60%, 80% and 100%. These mix ratios were defined by mass and according to the granulometry of the materials used. Blocks molded with each mix ratio were tested according to the NBR 15116 standard, and the results were compared with the reference ratio and the NBR 6136 standard. The blocks with recycled aggregates showed increased water absorption, reduction in specific mass and reduction in compressive strength. These variations were proportional to the aggregate replacement ratios. According to the statistical analysis of the tests results, only the blocks molded with 20% of recycled aggregates showed no significant decrease in physical and mechanical properties when compared to the reference mix ratio. These blocks were also the only ones, apart from those molded with the reference ratio, to meet the compressive strength and water absorption requirements defined by the NBR 6136 standard.